Peran Konseling Islam dalam Membantu Siswa Mengatasi Krisis Identitas Remaja di Sekolah - Haikal Hamdul Kamil; Siti Masrifah; Suci Triana; Hidayani Syam (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Abstrak. A psychosocial phenomenon often experienced by adolescents, especially in the era of globalization influenced by technology and social media, is known as an identity crisis. In this phase, adolescents try to find their own identity and answer questions about their life goals, which often causes confusion, which has an impact on their psychosocial development. Islamic counseling plays an important role in helping adolescents overcome identity crises in a way that incorporates religious principles into their daily lives. This study was conducted to examine the role of Islamic counseling in helping adolescents overcome identity crises. The research method used was a qualitative approach with a library research design. This study analyzed various literature related to Islamic counseling, adolescent psychology, and the concept of identity crisis to identify how Islamic counseling can be applied as a solution for adolescents experiencing an identity crisis. The results of the study indicate that Islamic counseling can help individuals develop a strong self-identity based on the teachings of the Qur'an and Hadith, and help them live a life in harmony with Islamic values. It is hoped that this study can provide guidelines for teachers, counselors, and parents in providing support to adolescents facing an identity crisis.